Relationship Between Knowledge And Innovation Performance: The Mediating Role Of Absorptive Capacity - Khoo, Kah Kheng (2008)

(untitled)
Kepesatan dalam bidang teknologi telah mewujudkan daya saing di antara sector perindustrian terutama dalam bidang inovasi.